2017
DOI: 10.3847/1538-4357/aa5e4e
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoacoustic Waves in a Stratified Atmosphere with a Magnetic Null Point

Abstract: We perform nonlinear MHD simulations to study the propagation of magnetoacoustic waves from the photosphere to the low corona. We focus on a 2D system with a gravitationally stratified atmosphere and three photospheric concentrations of magnetic flux that produce a magnetic null point with a magnetic dome topology. We find that a single wavepacket introduced at the lower boundary splits into multiple secondary wavepackets. A portion of the packet refracts towards the null due to the varying Alfvén speed. Waves… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 90 publications
(188 reference statements)
3
29
0
Order By: Relevance
“…For example, the periodicity of current sheet reversals observed in simulations more representative of the solar atmosphere, with model transition regions, dipole fields and external wave driving (e.g. OR occurring in setups similar to Tarr et al 2017) may be meaningful despite the requirement to use relatively high resistivity in such models (e.g. S = 10 would be typical).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the periodicity of current sheet reversals observed in simulations more representative of the solar atmosphere, with model transition regions, dipole fields and external wave driving (e.g. OR occurring in setups similar to Tarr et al 2017) may be meaningful despite the requirement to use relatively high resistivity in such models (e.g. S = 10 would be typical).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the period of OR is dependent upon the initial disturbance to the null point field, behaving akin to a damped harmonic oscillator , and therefore a deeper understanding of null collapse can enhance our understanding of OR. This may be achieved by either simple assumptions regarding the proportion of available wave energy reaching close to the null, which would be equated to the null collapse system considered here as the initial perturbation energy, or with complementary numerical modelling efforts to estimate how much wave energy makes it to the immediate vicinity of the null whilst accounting for effects such as mode-conversion and atmospheric stratification [e.g., Tarr et al, 2017]. Indeed, our results could be used in tandem with globalscale simulations of these processes, which by necessity cannot resolve the details of the current sheet and reconnection dynamics.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Therefore, we would like to caution the reader that the definition of linear wave energy density and flux does not represent the total energy density and flux associated with a wave. To get a better estimate of the energy density and flux, we would have to include the second order terms (Leroy 1985;Tarr et al 2017). Having a time dependent background and spatial inhomogeneity, it is evident that the total wave energy is not conserved.…”
Section: Energy Transportmentioning
confidence: 99%